IT governance mechanisms at universities: an exploratory study - Bianchi, I. S.; Sousa, R. D.; Pereira, R. (Strategic and Competitive Use of Information Technology (SCUIT), 2017)
The pervasive use of technology has created a critical dependency on IT that requires particular attention to IT Governance (ITG). A set of ITG mechanisms involving structures, processes and relational mechanisms can be considered to implement IT governance and enhance business/IT alignment. Universities are organizations with a specific context and depend on IT for the success in teaching and learning, research and service. However, ITG implementation in universities has not received much attention and research in this type of organization is scarce. Therefore, the purpose of this research is to identify the most appropriate set of ITG mechanisms for universities. Semi-structured interviews with CIOs in ten universities from five countries were carried out. This research proposes six new ITG mechanisms to be added to the current set of ITG mechanisms. This research concludes by presenting the limitations and future work.